CARD14-associated papulosquamous eruption: A spectrum including features of psoriasis and pityriasis rubra pilaris. - Craiglow, Brittany G; Boyden, Lynn M; Hu, Ronghua; Virtanen, Marie; Su, John; Rodriguez, Gabriela; McCarthy, Catherine; Luna, Paula; Larralde, Margarita; Humphrey, Stephen; Holland, Kristen E; Hogeling, Marcia; et al. (J Am Acad Dermatol, 2018)
BACKGROUND: Heterozygous mutations in caspase recruitment domain family member 14 gene (CARD14) have been shown to be associated with psoriasis and familial pityriasis rubra pilaris (PRP). Many subjects with CARD14 mutations display features of both disorders, which can result in diagnostic uncertainty. In addition, these eruptions are often recalcitrant to conventional psoriasis therapies such as methotrexate, oral retinoids, and tumor necrosis factor-α inhibitors. OBJECTIVE: We sought to describe the clinical characteristics, family history, and response to therapy in subjects with papulosquamous eruptions due to mutations in CARD14. METHODS: Subjects were referred for genetic testing as part of a registry of subjects with inherited disorders of keratinization. DNA was isolated from blood or saliva, and multiplex targeted sequencing or whole exome sequencing was performed. Clinical histories of subjects with CARD14 mutations were reviewed. RESULTS: We identified 15 kindreds with CARD14-associated papulosquamous eruption (CAPE). Characteristic features of CAPE include early age of onset; prominent involvement of the cheeks, chin, and ears; family history of psoriasis or PRP; minimal response to conventional topical and systemic psoriasis therapies; and improvement with ustekinumab. LIMITATIONS: Relatively small sample size. CONCLUSIONS: Many subjects with CARD14 mutations display characteristics of both psoriasis and PRP. We propose the term CARD14-associated papulosquamous eruption to describe this spectrum of disease. Subjects with clinical features suggestive of CAPE should undergo CARD14 sequencing and may benefit from treatment with ustekinumab.
Keywords: Age of Onset; CARD Signaling Adaptor Proteins; Child; Child, Preschool; Dermatologic Agents; Facial Dermatoses; Genetic Testing; Guanylate Cyclase; Humans; Infant; Infant, Newborn; Membrane Proteins; Phenotype; Pityriasis Rubra Pilaris; Psoriasis; Retreatment; Skin Diseases, Papulosquamous; Ustekinumab

Somatic Mutations in NEK9 Cause Nevus Comedonicus. - Levinsohn, Jonathan L; Sugarman, Jeffrey L; McNiff, Jennifer M; Antaya, Richard J; Choate, Keith A (Am J Hum Genet, 2016)
Acne vulgaris (AV) affects most adolescents, and of those affected, moderate to severe disease occurs in 20%. Comedones, follicular plugs consisting of desquamated keratinocytes and sebum, are central to its pathogenesis. Despite high heritability in first-degree relatives, AV genetic determinants remain incompletely understood. We therefore employed whole-exome sequencing (WES) in nevus comedonicus (NC), a rare disorder that features comedones and inflammatory acne cysts in localized, linear configurations. WES identified somatic NEK9 mutations, each affecting highly conserved residues within its kinase or RCC1 domains, in affected tissue of three out of three NC-affected subjects. All mutations are gain of function, resulting in increased phosphorylation at Thr210, a hallmark of NEK9 kinase activation. We found that comedo formation in NC is marked by loss of follicular differentiation markers, expansion of keratin-15-positive cells from localization within the bulge to the entire sub-bulge follicle and cyst, and ectopic expression of keratin 10, a marker of interfollicular differentiation not present in normal follicles. These findings suggest that NEK9 mutations in NC disrupt normal follicular differentiation and identify NEK9 as a potential regulator of follicular homeostasis.
Keywords: Adolescent; Adult; Child; Female; Fluorescent Antibody Technique; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation; Nevus; NIMA-Related Kinases; Prognosis; Skin Neoplasms; Young Adult

Somatic Activating RAS Mutations Cause Vascular Tumors Including Pyogenic Granuloma. - Lim, Young H; Douglas, Stephanie R; Ko, Christine J; Antaya, Richard J; McNiff, Jennifer M; Zhou, Jing; Choate, Keith A; Narayan, Deepak (J Invest Dermatol, 2015)
Keywords: Adolescent; Cell Proliferation; Child; Child, Preschool; Female; Gene Expression Regulation, Neoplastic; Granuloma, Pyogenic; Humans; Infant; Infant, Newborn; Male; Mutation; ras Proteins; Vascular Neoplasms

Whole-exome sequencing reveals somatic mutations in HRAS and KRAS, which cause nevus sebaceus. - Levinsohn, Jonathan L; Tian, Li C; Boyden, Lynn M; McNiff, Jennifer M; Narayan, Deepak; Loring, Erin S; Yun, Duri; Sugarman, Jeffrey L; Overton, John D; Mane, Shrikant M; Lifton, Richard P; Paller, Amy S; et al. (J Invest Dermatol, 2013)
Keywords: Adolescent; Adult; Amino Acid Sequence; Biopsy; Child; Child, Preschool; Cohort Studies; Epidermis; Exome; Humans; Infant; Middle Aged; Molecular Sequence Data; Mutation; Nevus, Sebaceous of Jadassohn; Proto-Oncogene Proteins; Proto-Oncogene Proteins p21(ras); ras Proteins; Sequence Analysis, DNA; Young Adult